Auction theory and a note on game mechanisms - Dushko Josheski; Elena Karamazova (Croatian Review of Economic, Business and Social Statistics (CREBSS), 2021)
This paper will review important topics on the subject of auction theory and mechanism design, these include: efficiency first and foremost, also revenue comparison between different types of auctions and the issue of incentive compatibility, individual rationality with the general idea and proof that bilateral trade is inefficient. Mechanism design theory tells us that if buyers and sellers both have private information full efficiency is impossible, however Vickrey auction (single unit auction) will be efficient i.e. will put the goods in the hands of the buyers that value them most. However, the conclusion from this paper is that because of overvaluation of bidders the main result is inefficient, i.e. bids are too high. When weak and strong bidders are compared the main conclusion is that strong bidders' expected payoff is higher in second price auction (SPA), while weak bidder prefers first price auction (FPA) bid.
Keywords: D44; D82; 330; asymmetric auctions; first price auction; Green-Laffont; Myerson-Satterthwaite; second price auction